Randomised comparison of G-CSF-mobilized peripheral blood mononuclear cells versus bone marrow-mononuclear cells for the treatment of patients with lower limb arteriosclerosis obliterans - Huang, Ping Ping; Yang, Xiao Feng; Li, Shan Zhu; Wen, Jin Chao; Zhang, Yan; Han, Zhong Chao (Thrombosis and Haemostasis, 2007)
Previous studies have suggested that the lower limb arteriosclerosis obliterans (LASO) could be improved by autologous transplantation of either bone marrow mononuclear cells (BMMNC) or G-CSF-mobilized peripheral blood mononuclear cells (M-PBMNC). However, the number of patients observed was very limited, and little information is available regarding comparison. The present randomised trial was designed to assess which is the better option. One hundred fifty patients with LASO were randomised to either group A (76 cases implanted with M-PBMNC) or group B (74 cases implanted with BMMNC), and followed up for 12 weeks. Primary outcomes were safety and efficacy of treatment, based on ankle-brachial index (ABI) and rest pain, and analysis was per protocol. Significant improvement of the main clinical index was observed in both groups after transplantation. No transplantation-related complication was observed in either group. Comparative analysis revealed that at 12 weeks after cell implantation, improvement of ABI (difference 0.06 ± 0.01; p<0.0001), skin temperature (difference 0.55 ± 0.25; p=0.028), and rest pain (difference –0.57 ± –0.15;p<0.0001) was significantly better in groupA patients than group B patients. However, there was no significant difference between two groups for pain-free walking distance, transcutaneous oxygen pressure, ulcers, and rate of lower limb amputation. Autologous transplantation of either M-PBMNC or BMMNC significantly promotes improvement of limb ischaemia in patients with LASO. Comparative analysis indicated that M-PBMNC should be more practical in comparison with BMMNC in the treatment of LASO.
Keywords: Peripheral vascular disease; angiogenesis; cells; therapy